Triflic Acid-Functionalized Silica-Coated Magnetic Nanoparticles as a Magnetically Separable Catalyst for Synthesis of gem-Dihydroperoxides - Liu, Yong-Hui; Deng, Jia; Gao, Jian-Wu; Zhang, Zhan-Hui (Advanced synthesis & catalysis, 2012)
Triflic acid‐functionalized silica‐coated magnetic nanoparticles [γ‐Fe2O3@SiO2‐TfOH] were readily prepared and identified as an effictive catalyst for the transformation of aldehydes or ketones into their corresponding gem‐dihydroperoxides with 30% aqueous hydrogen peroxide. The catalyst was easily separated by magnetic decantation and the recovered catalyst was reused for seven cycles without significant loss of catalytic activity.